THE RELATIONSHIP OF LEARNING MOTIVATION, DISCIPLINE OF STUDENTS AND RESPONSIBILITIES OF LEARNING STUDENTS ON THE LEARNING RESULTS OF MATHEMATICS STUDENTS OF SMA NEGERI 1 PLERET - Retno Nurhayati; Abdul Taram (Universitas Ahmad Dahlan, 2017)
Low student learning outcomes are influenced by many factors. Learning motivation, student discipline and student learning responsibilities are several factors related to learning outcomes. This study aims to determine whether or not there is a positive and significant relationship between learning motivation, student discipline and student learning responsibilities with mathematics learning outcomes of XI IPS students in the even semester of SMA Negeri 1 Pleret Bantul Regency 2015/2016 Academic Year. The population of this study were all students of class XI IPS even semester of SMA Negeri 1 Pleret Bantul Regency in the 2015/2016 Academic Year consisting of 3 classes with a total of 72 students. Samples were taken by random sampling technique and obtained class XI IPS 2 as a sample class. Data collection techniques were carried out using the test and questionnaire method. The test method was used to collect data on student learning outcomes, while the questionnaire method was used to collect learning motivation, student discipline, and responsibility data, answer learning. The instrument test uses a validity test, a different power test, and a reliability test. Analysis prerequisite test is a normality test, independent test, linearity test. Data analysis for hypothesis testing uses correlation analysis and linear regression analysis. The results showed that there was a positive and significant relationship between learning motivation, student discipline and learning responsibilities with learning outcomes Â dan so obtained . The multiple correlation coefficient (R) of 0.5998 with the regression equation Â the relative contribution of X1 = 32.984%, X2 = 35.149%, X3 = 31.867% with a double determination coefficient (R2) 0.3598 and effective contribution X1 = 11.868%, = 12.664%, X3 = 11.467%.